2021
DOI: 10.17762/turcomat.v12i2.1503
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Paddy Leaf Diseases using Evolutionary and Machine Learning Methods

Abstract: In the field of agriculture, especially paddy plants, there is a demand for research to classify the paddy diseases at early stages. This is feasible if there are automated systems that can assist the farmers to recognize the paddy diseases from the paddy leaf images of the plants. The recognition of agricultural plant diseases by utilizing the image-processing and machine learning techniques can certainly minimize the reliance on the farmers to protect the yield of paddy crops. In this paper, an attempt has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Authors in [73] have proposed an automated model using machine learning and evolutionary approaches to identify paddy leaves diseases. The model can be used on android platform for quick identification of diseases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Authors in [73] have proposed an automated model using machine learning and evolutionary approaches to identify paddy leaves diseases. The model can be used on android platform for quick identification of diseases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nilam et al, [1] Paddy leaf illnesses were identified utilising evolutionary and machine learning methods including AdaBoost and Bagging Classifier, as well as evolutionary algorithms like Genetic algorithm. In this proposed system they can obtained the accuracy by GA classifier is 96% at training feature-set and 91% at testing feature-set.…”
Section: Related Workmentioning
confidence: 99%